Approach to identification and classification of the key, strategic and critical minerals important for the mineral security of Poland. (March 2021) - Galos, Krzysztof; Lewicka, Ewa; Burkowicz, Anna; Guzik, Katarzyna; Kot-Niewiadomska, Alicja; Kamyk, Jarosław; Szlugaj, Jarosław
Abstract: The paper presents a proposal to designate the minerals of key, strategic and critical importance for the mineral security of Poland. Based on a review of the foreign and Polish literature, differences in defining the terms in question were pointed out. Taking into account existing solutions, the authors proposed a comprehensive methodology of designating key, strategic and critical minerals for Poland. 148 individual minerals were selected for analysis. When determining the key minerals, a criterion of average value of their annual consumption in Poland in the last decade was adopted. This approach had also regard to the general tendency of consumption of a given mineral and the net import reliance index. In the case of strategic minerals, a two-stage analysis was performed. In the first stage, the identification of potentially strategic minerals that are indispensable for the sectors defined as crucial for the country's economic security (based on an expert assessment) was performed. In the second stage, for selected potentially strategic raw materials, criteria of the average consumption value in recent years and the net imports reliance were applied. This was the basis for establishing the list of strategic minerals. To identify critical minerals, the methodology developed for the European Union with some significant modifications was adopted. Primarily, all the minerals previously classified as key and/or strategic were granted the status of high economic importance in Poland, while EU's evaluation of the value of economic importance (EI) indicator was disregarded. Additionally, the value of the supply risk index (SR), above which minerals were identified as critical, was slightly reduced in relation to that adopted for the European Union, i.e. from 1.0 to 0.9. On the basis of the analysis conducted, three lists comprising 42 key, 24 strategic and 17 critical minerals indispensable for the Polish economy development were proposed. Identification of these minerals is of fundamental importance for further works on the Mineral Policy of Poland. Highlights: 148 minerals analysed as key, strategic and critical for the Polish economy. Mean value of minerals' consumption in 2009–2018 decisive for key minerals. Use in industries of the country economic security decisive for strategic minerals. Modified EU methodology decisive for critical minerals for the Polish economy. Mineral policy of Poland is expected to be based on lists of these minerals.